Predictors of in-hospital mortality in critically ill patients with COVID-19: a large dual tertiary centre study. Issue 12 (1st December 2022) - Cirillo, Chiara; Nakou, Eleni; Georgiopoulos, Georgios; Tountas, Christos; Victor, Kelly; Marvaki, Apostolia; Desai, Nishita; Fisher, Richard; Ryan, Matthew; Demir, Ozan M; Corcoran, Eleanor; O'Gallagher, Kevin; et al.
Abstract : Objectives: The aim of this study was to investigate the relationship of echocardiographic parameters, laboratory findings and clinical characteristics with in-hospital mortality in adult patients with COVID-19 admitted to the intensive care units (ICU) in two large collaborating tertiary UK centres. Design: Observational retrospective study. Setting: The study was conducted in patients admitted to the ICU in two large tertiary centres in London, UK. Participants: Inclusion criteria were: (1) patients admitted to the ICU with a COVID-19 diagnosis over a period of 16 weeks. and (2) underwent a transthoracic echocardiogram on the first day of ICU admission as clinically indicated. No exclusion criteria applied. Three hundred patients were enrolled and completed the follow-up. Primary and secondary outcome measures: The outcome measure in this study was in-hospital mortality in patients admitted to the ICU with COVID-19 infection. Results: Older age (HR: 1.027, 95% CI 1.007 to 1.047; p=0.008), left ventricular (LV) ejection fraction<35% (HR: 5.908, 95% CI 2.609 to 13.376; p<0.001), and peak C reactive protein (CRP) (HR: 1.002, 95% CI 1.001 to 1.004, p=0.001) were independently correlated with mortality in a multivariable Cox regression model. Following multiple imputation of variables with more than 5% missing values, random forest analysis was applied to the imputed data. Right ventricular (RV) basal diameter (RVD1), RV mid-cavity diameter (RVD2), tricuspid annular plane systolic excursion, RV systolic pressure, hypertension, RV dysfunction, troponin level on admission, peak CRP, creatinine level on ICU admission, body mass index and age were found to have a high relative importance (> 0.7). Conclusions: In patients with COVID-19 in the ICU, both severely impaired LV function and impaired RV function may have adverse prognostic implications, but older age and inflammatory markers appear to have a greater impact. A combination of echocardiographic and laboratory investigations as well as demographic and clinical characteristics appears appropriate for risk stratification in patients with COVID-19 who are admitted to the ICU.